Modern paradigms research of the personal role structure of a future psychologist (Actual Problems of Psychology in Educational Institutions, 2022)
The article analyzes modern theoretical approaches to the understanding of the personal role structure. The basic characteristics of this phenomenon are determined, the connection between role structure and degree of personal role competence of the future psychologist is shown. Based on empirical research, justified the need to create a program for the development of professional roles of the future psychologist, adequate to the content of his professional activities.
Keywords: role; personal role structure; role-play theories of personality; role-play competence; role-play reflection; role-play depth; role-play repertoire